Application of Power Electronics Converters in Smart Grids and Renewable Energy Systems - Khan, Irfan Ahmad; Muyeen, S. M. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book focuses on the applications of Power Electronics Converters in smart grids and renewable energy systems. The topics covered include methods to CO2 emission control, schemes for electric vehicle charging, reliable renewable energy forecasting methods, and various power electronics converters. The converters include the quasi neutral point clamped inverter, MPPT algorithms, the bidirectional DC-DC converter, and the push-pull converter with a fuzzy logic controller.